Identification of A Novel SBF2 Frameshift Mutation in Charcot–Marie–Tooth Disease Type 4B2 Using Whole-exome Sequencing - Meiyan Chen; Jing Wu; Ning Liang; Lihui Tang; Yanhua Chen; Huishuang Chen; Wei Wei; Tianying Wei; Hui Huang; Xin Yi; Ming Qi (Genomics, Proteomics & Bioinformatics, 2014)
Charcot–Marie–Tooth disease type 4B2 with early-onset glaucoma (CMT4B2, OMIM 604563) is a genetically-heterogeneous childhood-onset neuromuscular disorder. Here, we report the case of a 15-year-old male adolescent with lower extremity weakness, gait abnormalities, foot deformities and early-onset glaucoma. Since clinical diagnosis alone was insufficient for providing pathogenetic evidence to indicate that the condition belonged to a consanguineous family, we applied whole-exome sequencing to samples from the patient, his parents and his younger brother, assuming that the patient’s condition is transmitted in an autosomal recessive pattern. A frame-shift mutation, c.4571delG (P.Gly1524Glufs∗42), was revealed in the CMT4B2-related gene SBF2 (also known as MTMR13, MIM 607697), and this mutation was found to be homozygous in the proband and heterozygous in his parents and younger brother. Together with the results of clinical diagnosis, this case was diagnosed as CMT4B2. Our finding further demonstrates the use of whole-exome sequencing in the diagnosis and treatment of rare diseases.